Production of palm-based diaclyglycerol olein and stearin through dry fractionation of palm-based diacylglycerol fat and its applications as cooking oil and bakery shortening - Abd Latip, Razam (2012)
This work was aimed at developing a novel fractional crystallisation process of palm-based diacylglycerol (PDAG) fat for production of palm-based diacylglycerol olein (PDAGL) and palm-based diacylglycerol stearin (PDAGS) for applications as cooking oil and bakery shortening. In the first part of this work, the effect of crystallisation temperature (Ct), cooling rate (Cr) and agitation speed (As) on physical and chemical properties of PDAGL and PDAGS were studied. It was noted that as Cr increased, the amount of palmitic acid, C16:0 and oleic acid, C18:1 in PDAGL increased (from 35.0 to 37.2%) and decreased (from 47.1 to 45.3%), respectively, resulting in decrease in iodine value (IV) (from 58.8 to 52.3). Similar trend was observed when Ct is increased, the amount of C16:0 increased from 33.5 to 38.7% and C18:1 decreased from 49.1 to 44.6%. Fast cooling produced PDAGS with lower amount of saturated fatty acid C16 and hence, contributed to higher IV. There is no correlation between physical and chemical properties of PDAGL and PDAGS with different As. Crystallisation process parameters namely Cr, Ct and As were optimized using dual response surface methodology (RSM) in lab scale. The optimal crystallisation process parameters were 1.0 C/min of Cr, 46 rpm of As and 37 C of Ct which yielded approximately 70 wt % of PDAGL with 58 IV. The optimal crystallisation process parameters can be further scaled-up to a 50 kg crystalliser for production of PDAGL with similar IV and percentage yield. The oxidative stability of PDAG oil and its olein fraction were investigated at 120 C by the rancimat method with and without addition of antioxidants. Heat stability test was conducted at 90 C for 5 days. Compared with TAG-based oils, the PDAGbased oil displayed lower oxidative stability due to lower content of tocopherols. The oxidative stability of PDAGL improved with addition of 1000 ppm tocopherols,1000 ppm citric acid, 200 ppm tertiary butyl hydroquinone (TBHQ) and mixture of 100 ppm BHT and 100 ppm BHA. Among all antioxidants, natural antioxidant, tocopherol and synthethic antioxidant, TBHQ showed highest oxidative stability improvement to the oil. The induction period (IP) of PDAGL increased from 10.26 0.28 to 13.58 0.43 and 19.72 0.36 h with addition of 1000 ppm tocopherol and 200 ppm TBHQ, respectively. The stability of palm olein (POL), PDAGL without antioxidant and with 1000 ppm tocopherol (PDAGL(T)) and 200 ppm TBHQ (PDAGL(Q)) under deep-frying conditions were investigated. PDAGL exhibited better IP than POL. However, the free fatty acid (FFA) increased 3 times faster in PDAGL compared to POL. The rate of FFA formation in PDAGL was 0.7 times lower when antioxidants were added. However, no significant difference (P>0.05) in FFA content was observed in PDAGL and PDAGL(Q). The initial IP of PDAGL (9.95 + 0.04 h) was increased upon addition of tocopherol (14.55+0.05 h) and TBHQ (17.83 + 0.04 h). PDAGL(T) showed slower reduction in the IP throughout frying process as compared to PDAGL(Q). However, additions of antioxidants to PDAGL showed no significant effect (P>0.05) in polymerized-glyceride (PG) and anisidine value (AV) produced throughout the frying due to oxidization of the antioxidants upon heating, thus decreasing their antioxidant activities. It can be concluded that PDAGL is suitable as cooking oil but not for industrial frying oil. The physicochemical properties including phase, melting and crystallisation behavior of shortening systems produced from PDAGS with palm-mid fraction (PMF), POL and sunflower oil (SFO) were studied. The results showed that PDAGS and PMF were hard fats while SFO was a softer oil than POL. Due to sharp melting points of PMF, the SFC profile of PDAGS/PMF was able to achieve the desired level of solid fat especially at body temperature for food application. The binary mixtures of PDAGS/SFO had very low SFC at temperature below 35oC as compared to PDAGS/POL. The melting profiles of PDAGS/PMF, PDAGS/POL and PDAGS/SFO had completely different low melting fraction (LMF) and medium melting fraction (MMF) but almost similar high melting fraction (HMF). Thermodynamic analysis of liquidus line showed that all binary mixtures of PDAGS/ PMF, PDAGS/POL and PDAGS/SFO had ideal mixing behavior where the calculated liquidus line reproduced well with the experimental points in phase diagram. The iso-solid diagram constructed showed that no eutectic behavior existed in all binary mixtures. However, the iso-solid lines of PDAGS/POL lacked structural complementary between high and low percentage of SFC line, while PDAGS/SFO not well constructed at high percentage of SFC line. The results from X-Ray Diffractometer (XRD) analysis showed that both binary mixtures of PDAGS/PMF and PDAGS/SFO were crystallized in β’+β polymorphs at XPDAGS = 0.4 to XPDAGS = 0.5, while all the binary mixtures of PDAGS/POL were crystallized in β polymorphs. Overall analyses results gave indication that PDAGS and PMF blend was the most suitable fat blend to be used as bakery shortening.